Merging the Multi-Target Effects of Kleeb Bua Daeng, a Thai Traditional Herbal Formula in Unpredictable Chronic Mild Stress-Induced Depression - Juthamart Maneenet; Orawan Monthakantirat; Supawadee Daodee; Chantana Boonyarat; Yutthana Chotritthirong; Pakakrong Kwankhao; Supaporn Pitiporn; Suresh Awale; Yaowared Chulikhit (MDPI AG, 2021)
Major depressive disorder (MDD) is a common and debilitating psychiatric disease characterized by persistent low mood, lack of energy, hypoactivity, anhedonia, decreased libido, and impaired cognitive and social functions. However, the multifactorial etiology of MDD remains largely unknown due the complex interaction between genetics and environment involved. Kleeb Bua Daeng (KBD) is a Thai traditional herbal formula that has been used to promote brain health. It consists of a 1:1:1 ratio of the aerial part of Centella asiatica, Piper nigrum fruit, and the petals of Nelumbo nucifera. According to the pharmacological activities of the individual medicinal plants, KBD has good potential as a treatment for MDD. The present study investigated the antidepressant activity of KBD in an unpredictable chronic mild stress (UCMS) mouse model. Daily administration of KBD to UCMS mice ameliorated both anhedonia, by increasing 2% sucrose intake, and hopeless behavior, by reducing immobility times in the forced swimming test (FST) and tail suspension test (TST) without any effect on locomotor activity. The mechanism of KBD activity was multi-modal. KBD promoted neurogenesis by upregulation of brain-derived neurotrophic factor (BDNF) and cyclic AMP-responsive element binding (CREB) mRNA expression in the frontal cortex and hippocampus. Daily treatment with KBD significantly reversed UCMS-induced HPA axis dysregulation by upregulating the glucocorticoid receptor (GR) while downregulating serum- and glucocorticoid-inducible kinase 1 (SGK1) and FK506 binding protein 5 (FKBP5) mRNA expression. KBD treatment also normalized proinflammatory cytokine expression including tumor necrosis factor-alpha (TNF-α), and interleukin (IL)-1β and IL-6. KBD and its component extracts also exhibited an inhibitory effect in vitro on monoamine oxidase (MAO) A and B. The multiple antidepressant actions of KBD emphasize its potential as an effective, novel treatment for MDD.